Effect of Melt Superheat and Alloy Size on the Mixing Phenomena in Argon‐Stirred Steel Ladles. Issue 4 (30th August 2018) - Duan, Haojian; Zhang, Lifeng; Thomas, Brian G.
Abstract : In the current study, the melting and mixing behavior of the alloy in argon‐stirred steel ladles is simulated based on the turbulent fluid flow. The formation of the solidified steel shells around cold ferroalloy particles is considered and the discrete phase model is adopted to predict the motion of ferroalloy particles. Ferroalloy particles are heated by the surrounding liquid during their travel trajectories and the mixing of dissolved alloy solute is described by the species transport model as the steel shell disappears. User defined functions are used to record the melting time and the trajectory length of each ferroalloy particle, as well as to check the mixing criteria in every cell and predict the local mixing time in the entire computational domain. Mixing time maps which visualize the mixing efficiency are obtained as a novel representation to describe the local mixing time in the entire ladle. The effects of the superheat of the melt and the diameter of alloy particles are investigated. The results show that the higher superheat of the melt and the smaller size of alloy particle facilitate the melting and mixing of the alloy in argon‐stirred steel ladles. Abstract : The melting and mixing behavior of the alloy in argon‐stirred steel ladles is simulated based on the turbulent fluid flow. Mixing time maps are obtained by checking the mixing criteria in every cell using user defined functions. The higher superheat of the melt and the smaller size of alloy particle facilitate the melting and mixing process.